THEORETICAL FOUNDATIONS OF DIRECT TAXATION OF COMMERCIAL BANKS IN UZBEKISTAN (American Journal of Business Management, Economics and Banking, 2025)
In the world, commercial banks are the main link in today's economic growth. Banks receive the main profit in the form of a deposit and without a deposit. In addition, commercial banks own high-value real estate and land. The listed income is subject to taxation by commercial banks.This abstract is devoted to taxes paid by commercial banks in Uzbekistan and their role in the structure of state budget revenues. It is also written about the tax burden of commercial banks in Uzbekistan and their share in the the shadow economy.